Contributions to the knowledge of the “Staphylinus-complex” (Coleoptera, Staphylinidae, Staphylinini) of China. Part 11. The genus Wasmannellus Bernhauer, 1920 and Nelmanwaslus gen. nov. - Smetana, Aleš (Zootaxa, 2006)
The monotypic genus Wasmannellus Bernhauer, 1920 is redescribed and reevaluated; its relationship with the relevant genera of Staphylinini is briefly discussed; the appropriate portion of the key to genera in Smetana & Davies (2000) is modified to allow the inclusion of the genus. The genus Nelmanwaslus is described as new, with N. ornatus spec. nov. as the type species and another included species: N. stevensi (Cameron, 1932) (comb. nov., from Wasmannellus). Nelmanwaslus is the genus that was misidentified as Wasmannellus in Smetana & Davies (2000).